Pemodelan Integrasi Data Barang Milik Negara di Perguruan Tinggi Menggunakan Metode ETL (Extract, Transform, Load) dengan Pentaho - Purwita Sari; Lucky Indra Kesuma; Mira Afrina; Dedy Kurniawan (The Indonesian Journal of Computer Science, 2024)
Strategic transformation and technological innovation in the realm of governments require officials to adapt to new perspectives. Efforts to increase the efficiency of the bureaucratic system and improve public services are directed at realizing ideal government governance. This research aims to build a data integration model for Higher Education State Property (BMN) using the ETL (Extract, Transform, Load) method using Pentaho. Researchers used the ETL method because the function of the asset module in the SAKTI Application, such as the room goods list (DBR), was not optimal, which made it difficult for the BMN team in the inventory process. Usually, an inventory is carried out using the SITARI application to identify recorded items and their location. The steps taken are to reconcile the BMN data in the SIMAN application with the procurement documents, then import the appropriate data into the SITARI application. Considering the large amount of BMN data, it is still possible for operator errors to occur in matching the data. This research is expected to produce an integration model that can reduce the level of data synchronization errors and make it easier for the BMN team to present more accurate reports.